Investigation of isophorone diisocyanate oligoisocyanurate effect on wa-ter dispersible polyurethane properties - Karpov, S.V.; Dzhalmukhanova, A.S.; Chernyayev, D.A.; Lodygina, V.P.; Komratova, V.V.; Malkov, G.V.; Badamshina, E.R. (KSU publ., 2020)
Oligoisocyanurates (OIC) are the products of various diisocyanates cyclotrimerization reaction, with their func-tionality being more than three (potential crosslinking agents). They are applicable in chemical polymer indus-try as an additive to diisocyanates for polyurethane coatings obtaining with various properties, as well as an isocyanate-containing component on its own for polyurethane synthesis. The OIC-based polymers possess a number of unique properties, e.g. improved thermal stability, fire resistance, UV resistance, also they are not expected to undergo hydrolysis. We studied the effect of isophorone diisocyanate oligoisocyanurate content on hydrodynamic, thermo-mechanical and thermal properties of resulting water dispersible polyurethanes. Sam-ples of water dispersible polyurethanes containing isophorone diisocyanate (IPDI), poly (butylene adipate) (PBA) and 2,2-dimethylolpropionic acid (DMPA) were prepared following acetone method for this purpose, with IPDI OIC amount being 10–30 wt.% per pure IPDI. IPDI OIC was partially blocked with morpholine to exclude crosslinking in WDPU synthesis. Dynamic mechanical analysis (DMA), differential scanning calorim-etry (DSC), and dynamic light scattering (DLS) were used to characterize the polymers obtained. It was estab-lished that oligoisocyanurates improve the characteristics of both water dispersible polyurethanes and their polymer films. Moreover, oligoisocyanurates prevent polyurethane coatings crystallization due to its branched structure, which without a doubt will affect their performance positively.
Keywords: polyurethane